Developing a framework of Islamic bank operational risk management: ‘people risk’ - Aisyah Abdul Rahman; Zaleha Yazid (Penerbit Universiti Kebangsaan Malaysia, 2015)
The study of human resource has become a crucial topic in understanding the determinants of operational risk. Given the various sources of operational risk, losses resulting from staff performance seemed to be the major cause as employees are the key players who manage the processes and systems of undesired events. This study explored the influence of staff performance attributes toward operational risk management, with a focus on ‘people risk’. The study was conducted using qualitative approach via face-to-face and telephone interviews with 14 respondents from 7 Islamic banks in Malaysia. Our preliminary finding showed that training, education, experience and compensation lead toward better management of ‘people risk’. Hence, a clear understanding of the factors affecting ‘people risk’ would help ensuring an effective and successful strategy in managing human resources especially in developing the operational risk management framework for the Islamic banking institutions.